2004
DOI: 10.1128/iai.72.6.3195-3203.2004
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Differentiation Antigen 88 Deficiency Impairs Pathogen Clearance but Does Not Alter Inflammation inBorrelia burgdorferi-Infected Mice

Abstract: The spirochete Borrelia burgdorferi causes acute inflammation in mice that resolves with the development of pathogen-specific adaptive immunity. B. burgdorferi lipoproteins activate innate immune cells via Toll-like receptor 2 (TLR2), but TLR2-deficient mice are not resistant to B. burgdorferi-induced disease, suggesting the involvement of other TLRs or non-TLR mechanisms in the induction of acute inflammation. For this study, we used mice that were deficient in the intracellular adapter molecule myeloid diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
161
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(187 citation statements)
references
References 42 publications
23
161
3
Order By: Relevance
“…Interestingly, the lack of IL-12 production via limited TLR activation during the inflammatory/immune response appears to lead to Th2 responses, suggesting that this type of response is a default pathway that occurs in the absence of IL-12. Investigations have demonstrated that MyD88 knockout mice were not able to generate a Th1 response when challenged with an infectious agent (57)(58)(59)(63)(64)(65)(66). Also, MyD88-mediated cytokines appear to provide a suppressive signal for a Th2-type response.…”
Section: Notch Ligands Regulate Cytokine-dependent Responses and Partmentioning
confidence: 99%
“…Interestingly, the lack of IL-12 production via limited TLR activation during the inflammatory/immune response appears to lead to Th2 responses, suggesting that this type of response is a default pathway that occurs in the absence of IL-12. Investigations have demonstrated that MyD88 knockout mice were not able to generate a Th1 response when challenged with an infectious agent (57)(58)(59)(63)(64)(65)(66). Also, MyD88-mediated cytokines appear to provide a suppressive signal for a Th2-type response.…”
Section: Notch Ligands Regulate Cytokine-dependent Responses and Partmentioning
confidence: 99%
“…The lipoproteins expressed by B. burgdorferi are known to vary widely under the different environmental conditions they encounter during their natural infection cycle between arthropod and vertebrate hosts (15)(16)(17), but all of these proteins are predicted to possess similar triacyl modifications on their N-terminal cysteine residues (18). Studies from a number of laboratories have shown that these triacylated lipoproteins directly activate different host immune cells by signaling through TLR2 (19 -23) and the common intracellular adaptor molecule MyD88 (24,25). These interactions are further enhanced by the binding of lipoproteins to CD14 (26,27), which can increase the sensitivity of TLR2-lipoprotein interactions at physiological levels and augment TLR2-mediated activation (28).…”
mentioning
confidence: 99%
“…Mice deficient in TLR2 have increased spirochete loads and ankle swelling. However, mice lacking MyD88, an adapter required for signaling through TLR2 and several other pattern receptors, have even higher spirochete loads, suggesting multiple pathways respond to B. burgdorferi antigens [79][80][81][82]. Most likely, the phenotypes of these mutations result from poor recognition of B. burgdorferi components by phagocytic and antigen-presenting cells.…”
Section: Mammalian Components Affecting B Burgdorferi Infectionmentioning
confidence: 99%